Ischemic Stroke Risk Factors in Siloam Lippo Village Teaching Hospital - Astra Dea Simanungkalit; Chand Dhiraj Nagpal; Yesenia Tannu Martono; Yusak Mangara Tua Siahaan (Universitas Pelita Harapan, 2025)
Introduction: Acute ischemic stroke is the second leading cause of death worldwide and considered a major health problem leading to significant disability and mortality. Stroke Risk factors epidemiology various among population. This study conducted to identify stroke risk factors in Siloam Lippo Village, a secondary teaching hospital in Banten Province, Indonesia. Methods: This is a cross sectional study of acute ischemic stroke in the Stroke Unit of Siloam Lippo Village Teaching Hospital over a period of 3 months from January 2020 to March 2020. Data regarding the patients’ clinical profile, medical history and diagnostic test results were collected then analyzed using spreadsheet and SPSS version 21.0 software. Results: Forty-eight subjects met inclusion criteria in this study, 25 (52.08%) were male and 23 (47.92%) were female with a mean age of 58.16 ±12.02 years old. The most common risk factor for ischemic stroke in this study is hypertension (83,33%), followed by cigarettes smoking (45,83%), dyslipidemia (51,67%), diabetes mellitus (37,5%), previous stroke (37,5%) and history of heart disease (31,25%). More than 90% of subjects with hypertension and diabetes were uncontrolled. Conclusions: The most common risk factor for ischemic stroke in this study is hypertension and cigarettes smoking, while dyslipidemia, diabetes mellitus, previous stroke and history of heart disease found in more than one-third of the subjects. Uncontrolled status for hypertension and diabetes were more than 90%.